Optical Super‐Localisation of Single Nanoparticle Nucleation and Growth in Nanodroplets. Issue 9 (18th April 2023) - Ciocci, Paolo; Valavanis, Dimitrios; Meloni, Gabriel N.; Lemineur, Jean‐François; Unwin, Patrick R.; Kanoufi, Frédéric
Abstract: Invited for this issue's Front Cover are the groups of Prof. Frédéric Kanoufi, Université Paris Cité‐CNRS (France), and Prof. Patrick Unwin, University of Warwick (United Kingdom), collaborating under the EU Horizon 2020 'Single‐entity Nanoelectrochemistry' programme. The cover picture illustrates the use of their hybrid technique to investigate the dynamics of the electrodeposition of individual Ag nanoparticles within an ensemble. The particles are represented by band members whose individual performances can be monitored. Read the full text of the Research Article at 10.1002/celc.202201162 . Abstract :